Quetiapine abuse in illicit drug users or dealers: to screen or not to screen? Quetiapine abuse: A regional study - Gören, İsmail Ethem and Dağlıoğlu, Nebile (The Bulletin of Legal Medicine, 2021)
Objectives: Abuse of psychoactive drugs for therapeutic purposes is becoming more common due to their addiction potential. In many studies, quetiapine has been reported to be abused with illicit drugs. We aimed to point to the abuse and addiction potential of quetiapine by the rates of quetiapine abuse in blood samples of 4293 cases who came to our Forensic Toxicology Laboratory by using LC/MS/MS method. Methods: All cases who were caught by law enforcement officers while using or trading drugs as a requirement of the judicial process initiated were drug users or dealers and then they were brought to our forensic toxicology laboratory to obtain blood and urine samples. Quantification in blood samples was performed in routine laboratory analysis. The cases were asked whether they used any prescription drugs. The therapeutic drug users were excluded in this study. Results: Quetiapine was positive in 50 of 4293 cases (1.16 %). 93.8 % (n=4028) the all of the cases and all of the positive quetiapine were male. While quetiapine was used alone in 11 of 50 cases with quetiapine positivity, quetiapine was used simultaneously with one or more group of illicit drugs in the remaining 39 cases. Conclusions: In this study, the most common use of cannabis and quetiapine was determined in cases with drugs of abuse. The monitoring of quetiapine is essential for preventing drug abuse especially in prone population such as illicit drug abusers and addicts. Forensic Toxicology Laboratories play an important role in taking necessary preventions related drug abuse.